2003
DOI: 10.1038/sj.onc.1207274
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and overexpression of E2F3 in human bladder cancer

Abstract: We demonstrate that, in human bladder cancer, amplification of the E2F3 gene, located at 6p22, is associated with overexpression of its encoded mRNA transcripts and high levels of expression of E2F3 protein. Immunohistochemical analyses of E2F3 protein levels have established that around one-third (33/101) of primary transitional cell carcinomas of the bladder overexpress nuclear E2F3 protein, with the proportion of tumours containing overexpressed nuclear E2F3 increasing with tumour stage and grade. When cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
119
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 25 publications
13
119
1
Order By: Relevance
“…In a previous study, we reported amplification of both E2F3 and CDKAL1 genes in the TCCSUP, 5637 and HT1376 bladder cancer cell lines (Feber et al, 2004). We also demonstrated that in all these three cell lines, amplification of the E2F3 gene was accompanied by E2F3 mRNA overexpression and high-level expression of the E2F3 proteins.…”
Section: Knockdown Of Mrna In Bladder Cancer Cells Containing Amplifisupporting
confidence: 62%
See 3 more Smart Citations
“…In a previous study, we reported amplification of both E2F3 and CDKAL1 genes in the TCCSUP, 5637 and HT1376 bladder cancer cell lines (Feber et al, 2004). We also demonstrated that in all these three cell lines, amplification of the E2F3 gene was accompanied by E2F3 mRNA overexpression and high-level expression of the E2F3 proteins.…”
Section: Knockdown Of Mrna In Bladder Cancer Cells Containing Amplifisupporting
confidence: 62%
“…The presence of this amplification was shown to correlate with tumour grade Prat et al, 2001) and, in high-grade cancers, with tumour cell proliferation rate (Tomovska et al, 2001). Initial mapping studies indicated that the 6p22 amplicon spanned the SOX4, PRL and E2F3 genes (Bruch et al, 2000;Veltman et al, 2003) and in CGH studies onto cDNA microarrays, we found that only two genes from this region, E2F3 and CDKAL1/FLJ20342 (hereafter called CDKAL1), were consistently amplified in bladder cancers (Feber et al, 2004). Amplification of E2F3 was accompanied by overexpression of the mRNA transcripts and E2F3 protein.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…We recently demonstrated that amplification and overexpression of E2F3 may represent a facilitating mechanism in the genesis of bladder carcinogenesis (Feber et al, 2004). High levels of expression of E2F3 were observed in approximately one-third of transitional cell carcinomas of the bladder, with the proportion of each tumour exhibiting E2F3 overexpression increasing with tumour grade and stage.…”
Section: Introductionmentioning
confidence: 99%